Pedicled perforator flaps for mid-tibial soft tissue reconstruction in medically compromised patients. (June 2020) - Jakubietz, Rafael G.; Schmidt, Karsten; Holzapfel, Boris M.; Meffert, Rainer H.; Jakubietz, Michael G.
Abstract: Background: The soft tissue of the central pretibial area is difficult to reconstruct often requiring free tissue transfer. Especially medically compromised patients are not ideal candidates for free tissue transfer and may benefit from expeditiously harvested local flaps with limited donor site morbidity. As muscle flaps are rare, pedicled flaps based on lateral perforators represent an alternative as the arc of rotation can often be limited to 90°. Material and Methods: A retrospective analysis of patient data was conducted to identify patients over the age of 60 years with comorbidities that underwent pretibial soft tissue reconstruction with a single-pedicle perforator flap. Patient demographics, size and cause of the defect, flap dimension, arc of rotation and complications were recorded. Results: Five patients with an average age of 71.4 years were included. The arc of rotation was 69°, all flaps healed. There were two recurrences of osteomyelitis. Conclusion: Lateral perforators originating from the anterior tibial artery or peroneal artery are adequate source vessels for single pedicled perforator flaps even in medically compromised patients. A perforator located proximal to the defect allows limiting the arc of rotation to less than 90°, which increases the safety of the flap. Patients benefit from a simple procedure without a microvascular anastomosis and a donor site confined to one extremity.